2016
DOI: 10.1007/s00423-016-1544-7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of intraoperative neural monitoring to preservation of the external branch of the superior laryngeal nerve: a randomized prospective clinical trial

Abstract: IONM contributes to visual and functional identification of the EBSLN and decreases the rate of EBSLN injury during superior pole dissection. Routine use of IONM to identify the EBSLN will minimize the risk of injury during thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 39 publications
0
56
0
7
Order By: Relevance
“…Barczynski et al (20) randomized 210 patients to undergo thyroidectomy without or with nerve monitoring and reported a rate of identification of 34% versus 84% respectively (P<0.01). More recently, Uludag et al (24) documented visual identification-only in 35% of the cases in which EBSLN recognition was attempted in this study, as compared to 65% after searching it with the probe. Hurtado-López et al (71) reported an identification rate of 97% of cases under IONM versus 79% without it.…”
Section: Intraoperative Ebsln Identification and The Role Of Ionmmentioning
confidence: 46%
See 4 more Smart Citations
“…Barczynski et al (20) randomized 210 patients to undergo thyroidectomy without or with nerve monitoring and reported a rate of identification of 34% versus 84% respectively (P<0.01). More recently, Uludag et al (24) documented visual identification-only in 35% of the cases in which EBSLN recognition was attempted in this study, as compared to 65% after searching it with the probe. Hurtado-López et al (71) reported an identification rate of 97% of cases under IONM versus 79% without it.…”
Section: Intraoperative Ebsln Identification and The Role Of Ionmmentioning
confidence: 46%
“…This so-called "human communicating nerve" is of special interest in intraoperative nerve monitoring (IONM) of the EBSLN, for it allows the recording of electroneuromyography (EMG) waveforms elicited by electrical stimulation by endotracheal surface electrodes (19). This finding is reinforced by several studies that found clear-cut TAM activity provoked by EBSLN stimulation in 70% to 100% of patients undergoing thyroid surgery (20)(21)(22)(23)(24). Darr et al (22) found that EBSLN-evoked potential of the TAM could be recorded in all cases when a tube with dedicated surface EMG electrodes in contact with the anterior aspect of the vocal cords was employed.…”
Section: Anatomy Of the Ebslnmentioning
confidence: 99%
See 3 more Smart Citations